A Comparison of Genetic Programming with Genetic Algorithms for Wire Antenna Design. (11th May 2008) - Williams, P. J.; Molteno, T. C. A.
Abstract : This work compares the performance of genetic programming (GP) against traditional fixed-length genome GA approaches on the optimization of wire antenna designs. We describe the implementation of a GP electromagnetic optimization system for wire structures. The results are compared with the traditional GA approach. Although the dimensionality of the search space is much higher for GP than GA, we find that the GP approach gives better results than GA for the same computational effort. In addition, we find that a more expressive antenna structure grammar, dramatically, improves the performance of the GP approach.